LITERATUR REVIEW : HUBUNGAN POLA HIDUP SEDENTER DENGAN PENURUNAN KEBUGARAN JASMANI PADA MAHASISWA - Maulana Akhmad Shah Ketaren; Michael Fito Siburian; Muhammad Arrafi; Habib Alfadli Nasution; Nimrot Manalu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This literature review examines the relationship between sedentary lifestyles and decreased physical fitness among university students. In recent years, the prevalence of sedentary behavior has increased significantly among students due to technological advancements, academic demands, and lifestyle changes. Even students in physical education and sports programs are not immune to the negative effects of prolonged sitting. This study analyzed empirical findings from 2020 to 2025, focusing on physical activity levels, sedentary behavior, and physical fitness outcomes across various student populations. The findings reveal a consistent negative correlation between sedentary lifestyles and physical fitness, although the strength of this relationship varies based on measurement tools, sample characteristics, and other lifestyle factors such as diet, sleep, and screen time. Some studies even suggest that regular physical activity can mitigate the negative effects of sedentary behavior, highlighting the complexity of this relationship. This review emphasizes the importance of reducing sedentary time and promoting more active lifestyles among students. It also identifies gaps in current research and recommends future studies to use longitudinal designs and objective measurement tools. These insights can guide educational institutions in developing effective health promotion programs tailored to student needs.